Trade Credit to Improve Financial Performance of Industry in Indonesia - Wahyuningtyas, Endah Tri; Fanani, Zaenal (SENTRALISASI, 2025)
This research investigates the role of credit sales as an effective strategy for enhancing financial performance. The study aims to assess the impact of credit sales on financial outcomes, employing panel data regression with a fixed effect model as the analytical method. The results indicate that credit sales have a positive and statistically significant influence on the financial performance of companies. Specifically, firms with higher levels of credit sales show a significant effect on Return on Assets (ROA), while those with lower levels of credit sales demonstrate a notable impact on Return on Equity (ROE). Additionally, the study reveals that bank loans and financial risk significantly attenuate the relationship between credit sales and financial performance. These findings provide valuable insights for managers in formulating credit sales strategies to enhance financial performance. Furthermore, the research contributes to the advancement of knowledge in financial management, offering a reference point for future studies in the field.